Penerapan Prinsip Ihsan Dalam Mendorong Pelayanan Prima Di Cafe Gadex Pacet Mojokerto - Wiyono, Joko (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2024)
This study aims to analyze the application of the Islamic principle of ihsan in enhancing service quality at Café Gadex, a micro-enterprise located in Pacet, Mojokerto. Ihsan, as a spiritual concept in Islam, encourages business actors to provide the best possible service ethically and responsibly, beyond mere material gain. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation. The findings indicate that the value of ihsan is embedded in the café's service culture, as reflected in the honesty, sincerity, and friendliness of the staff when serving customers. These values support the five dimensions of the SERVQUAL model: reliability, responsiveness, assurance, empathy, and tangibles. Most customers expressed satisfaction due to the warm, attentive, and family-like atmosphere. These findings affirm the perspectives of Hasan (2010) and Antonio (2001) that the integration of Islamic spiritual values can increase customer loyalty and enhance the business’s positive image. However, challenges remain, particularly in the provision of spiritual value training and maintaining consistency due to high employee turnover. The study recommends continuous Islamic-based training to ensure the sustainable implementation of ihsan in service delivery.